2000
DOI: 10.1161/01.atv.20.2.545
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Therapy Improves Endothelial Function in Type 2 Diabetes

Abstract: Abstract-A total of 75 in vivo endothelial function tests (intrabrachial artery infusions of endothelium-dependent[acetylcholine] and -independent [sodium nitroprusside] vasoactive agents) were performed in 18 type 2 diabetic patients (aged 58Ϯ2 years, body mass index 28.5Ϯ0.6 kg/m 2 , and fasting plasma glucose 229Ϯ11 mg/dL) and 27 matched normal subjects. These tests were performed before and 6 months after combination therapy with insulin and metformin and before and 6 months after metformin therapy only. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(70 citation statements)
references
References 60 publications
4
63
0
3
Order By: Relevance
“…Recently, Riddle et al [4] demonstrated that even a simple insulin regimen lowers HbA 1 c levels to 6.9% in type 2 diabetic patients. However, due to peripheral insulin resistance, most of the patients needed rather high insulin dosages [4,5]. In this and other trials, the insulin analogue glargine was shown to improve glycaemic control with significantly less nocturnal hypoglycaemia than NPH insulin [2][3][4]6].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…Recently, Riddle et al [4] demonstrated that even a simple insulin regimen lowers HbA 1 c levels to 6.9% in type 2 diabetic patients. However, due to peripheral insulin resistance, most of the patients needed rather high insulin dosages [4,5]. In this and other trials, the insulin analogue glargine was shown to improve glycaemic control with significantly less nocturnal hypoglycaemia than NPH insulin [2][3][4]6].…”
Section: Introductionmentioning
confidence: 70%
“…Currently, evidence is accumulating that insulin therapy in diabetic patients has rather beneficial effects on the cardiovascular system. It has been shown to normalise lipid abnormalities by reducing total plasma triglycerides and increasing plasma HDL-cholesterol, and also to improve endothelial function, determined by measuring forearm blood flow responses to endothelium-dependent vasodilators [5,6,9,10]. Furthermore, insulin exerts anti-inflammatory effects, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin therapy has been shown to improve fasting and postprandial brachial artery FMD [164,165] and FABF [166][167][168], possibly through reduced glycaemia and a direct increase in endothelial NO production through 1-phosphatidylinositol 3-kinase signaling [166,169]. Studies investigating the effects of sulphonylureas on ED have demonstrated inconsistent results in T2D patients [170][171][172].…”
Section: Antiglycemic Agents and Insulin Sensitizersmentioning
confidence: 99%
“…Besides the well-known benefit of insulin in the metabolic control of diabetic patients, some researchers also propose the existence of a cardioprotective action. Recent studies have shown that insulin exerts anti-inflammatory and anti-atherogenic effects and improves endothelial function (18)(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%